The finding of the distribution of a distance in an ovaloid by the method of the integral geometry - Gečiauskas, E. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Гячяускас. Нахождение распределения расстояния внутри овалоида методом интегральной геометрииE. Gečiauskas. Atstumo pasiskirstymo ovaloide nustatymas integralinės geometrijos metodu